PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA FISIK TERHADAP MOTIVASI DAN KEPUASAN KERJA KARYAWAN DI GRAND PUNCAK SARI RESTAURANT KINTAMANI - Sudana, I Wayan; Supartha, Wayan Gede (E-Jurnal Manajemen; Vol 4 No 7 (2015), 2015)
Job satisfaction of employees in a company very important role in order to create optimal performance. This study aimed to determine the effect of compensation and physical work environment for motivation and job satisfaction of employees. Sampling using nonprobability sampling method is sampling saturated with 45 respondents. Data analysis method used is the analysis of the path (path). The analysis showed that the compensation positive effect on motivation, physical work environment positive and significant effect on the motivation of compensation positive and significant effect on employee job satisfaction, physical work environment positive and significant effect on employee job satisfaction, motivation and significant positive effect on employee job satisfaction and motivation mediates the effect of compensation and physical work environment on employee job satisfaction. Based on the research results, the company should compensate embracing the principles of security, pay attention to the temperature of the air at the workplace, improve job security and do promotion.
Keywords: Compensation, Physical Work Environment, Motivation and Employee Satisfaction